355. CAMRELIZUMAB COMBINED WITH CHEMOTHERAPY OR APATINIB AS NEOADJUVANT THERAPY FOR LOCALLY ADVANCED ESOPHAGEAL SQUAMOUS CELL CARCINOMA: A PHASE 2 TRIAL. (24th September 2022) - Qi, Yu; Meng, Xiangrui; Shan, Zhengzheng; Fan, Qingxia; Wang, Feng
Abstract: At present, esophageal squamous cell carcinoma (ESCC) has a dismal prognosis with huge unmet clinical needs. Chemotherapy or angiogenesis inhibitor showed synergistic effects with immunotherapy in preclinical and clinical studies. With the potential benefit of combining PD-1 inhibitor with chemotherapy or angiogenesis inhibitor, we conducted a phase 2 trial (NCT03917966) to assess the efficacy and safety of camrelizumab plus chemotherapy or apatinib as neoadjuvant therapy for locally advanced ESCC. This is an open-label, non-randomized phase 2 trial of patients with stage cT2-4aN0-3 M0 ESCC. Cohort A enrolled patients who received 1 cycle of camrelizumab as induction therapy (200 mg Q3W) and 2 cycles of camrelizumab (200 mg Q2W) plus docetaxel and nedaplatin. Cohort B planned to enroll patients with 4 cycles of camrelizumab (200 mg Q2W) and apatinib (250 mg QD). Surgery was performed within 4–6 weeks after neoadjuvant therapy. The primary endpoint was major pathological response (MPR) rate. Secondary endpoints included pathological complete response (pCR) rate, R0 resection rate, disease-free survival, overall survival, and safety. Between Feb 2020 and Oct 2021, 62 patients were enrolled in cohort A, with a median age of 66 years. As of Apr 20, 2022, 59 patients completed neoadjuvant therapy and 48 completed surgery. In the surgery set, all patients reached R0 resection, 37 (77.1%) reached MPR, 19 (39.6%) reached pCR, and 44 (91.7%) had TNM downstaging. Any grade and grade ≥ 3 adverse events occurred in 88.7% and 14.5% of 62 patients, respectively. No new safety signals or treatment-related deaths were observed. Cohort B started recently, and only 2 of 40 planned patients had been enrolled, thus were not analyzed. Neoadjuvant camrelizumab in combination with chemotherapy in patients with locally advanced ESCC showed promising pathological response and downstaging effect with good tolerance. Another cohort of neoadjuvant camrelizumab plus apatinib for locally advanced ESCC is ongoing, which will be reported in the future.